INTEGRASI METODE PERBANDINGAN EKSPONENSIAL (MPE) DAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA BERPRESTASI - Octaviana Anugrah Ade Purnama; Sudarno Wiharjo; Yan Mitha Djaksana (Jurnal Sistem Informasi, 2021)
Today, the technology has been very rapid development where one of them is a web-based information system that is already widely used by agencies as a means of supporting the operational management. Utilization of information technology has also begun to be used by educational institutions for administration, promotion, information and others. SMK Wiyata Mandala Bogor is one of the educational institutions that has begun to use this technology, where several administrative systems have used desktop-based technology. SMK Wiyata Mandala Bogor is a foundation with SMP Wiyata Mandala Bogor, where if the students who wish to continue in SMK Wiyata Mandala Bogor will receive scholarships based on the learners' achievements during SMP Wiyata Mandala Bogor corresponding quota provided. Thus requiring a decision support system that can help the management of registration in providing scholarships. Decision support Metode Perbandingan Eksponensial (MPE) and Simple Additive Weighting (SAW) was chosen for the calculations could use an exponential rank of importance of subjects which will then be calculated based on the weight of a specified grade level. By using Metode Perbandingan Eksponensial (MPE) and Simple Additive Weighting (SAW) can produce a ranking of the best learners will receive scholarships in vocational Wiyata Mandala Bogor.